2011
DOI: 10.1016/j.jcf.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dyspnea and alveolar hypoventilation during exercise in cystic fibrosis: Impact of inspiratory muscle endurance

Abstract: Exertional dyspnea may be significantly influenced by inspiratory muscle function and alveolar hypoventilation in CF patients. Inspiratory muscle endurance could be of importance to analyse the impact of pulmonary rehabilitation in this specific disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
5
25
1
10
Order By: Relevance
“…3,4,28,29 Dunnink et al 4 suggest that the increased work of breathing due to airway obstruction could cause an effect of conditioning the respiratory muscles. On the contrary, some studies 5,12,30,31 showed a reduction of respiratory muscle strength, associating this finding with hyperinflation and malnutrition. Furthermore, Dassios et al 32 showed that maximum respiratory pressures were significantly diminished in subjects with no severe lung disease; however, no correlation between P Imax and BMI was found.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…3,4,28,29 Dunnink et al 4 suggest that the increased work of breathing due to airway obstruction could cause an effect of conditioning the respiratory muscles. On the contrary, some studies 5,12,30,31 showed a reduction of respiratory muscle strength, associating this finding with hyperinflation and malnutrition. Furthermore, Dassios et al 32 showed that maximum respiratory pressures were significantly diminished in subjects with no severe lung disease; however, no correlation between P Imax and BMI was found.…”
Section: Discussionmentioning
confidence: 95%
“…One previous study showed an apparent increase of endurance due to the adaptation of the muscles to the chronic stress of ventilating against a load generated by airway obstruction. 11 On the other hand, there is evidence that endurance may be diminished independent of nutritional status, the presence of airway obstruction, pulmonary hyperinflation, respiratory muscle strength, or maximum exercise capacity 3,12 and may be a major parameter to evaluate dyspnea in subjects with cystic fibrosis. 12 The individuals with cystic fibrosis who have a reduced capacity to contract the respiratory muscles become more susceptible to muscle fatigue with a limitation in the ability to carry out prolonged activities or tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspiratory muscle impairment in patients with CF has been studied in the literature using maximal respiratory pressures (8), diaphragmatic electromyography (10), the tension-time index of the respiratory muscles (2,3,9), and endurance testing by breathing against increased external loads (11,21,22). Although maximal respiratory pressures describe the pressure-generating capacity of the respiratory muscles at a given point of time, they would not be appropriate for the assessment or prediction of respiratory muscle function over time (14).…”
Section: Inspiratory Muscle Relaxation In Cf Articlesmentioning
confidence: 99%
“…Early recognition of respiratory muscle impairment may allow timely application of strategies aimed at preserving the functional integrity of the respiratory muscles, such as inspiratory muscle training (6) and noninvasive ventilation (7). Respiratory muscle dysfunction can be evaluated using a variety of measures, such as maximal respiratory pressures (8), the tension-time index of respiratory muscles (9), diaphragmatic electromyography (10), and inspiratory muscle endurance during exercise (11). However, the majority of these measures require the use of complex laboratory equipment and methodology and frequently involve invasive placement of catheters or electrodes, or repeated maximal forced maneuvres, which could be challenging for young or unwell patients with CF.…”
Section: Introductionmentioning
confidence: 99%